Answer:
2.7
Step-by-step explanation:
x^2=5.8*1.3=7.54
x=V7.54=2.7
Answer:
(x + 3)(x - 1)(x + 2)
Step-by-step explanation:
The fractions are:
![\dfrac{x + 2}{x^{2} + 2x - 3} \text{ and } \dfrac{x - 7}{x^{2} + 5x + 6}](https://tex.z-dn.net/?f=%5Cdfrac%7Bx%20%2B%202%7D%7Bx%5E%7B2%7D%20%2B%202x%20-%203%7D%20%5Ctext%7B%20and%20%7D%20%5Cdfrac%7Bx%20-%207%7D%7Bx%5E%7B2%7D%20%2B%205x%20%2B%206%7D)
Factor each denominator
![x^{2} + 2x - 3 = (x + 3)(x - 1)\\x^{2} + 5x + 6 = (x + 3)(x + 2)](https://tex.z-dn.net/?f=x%5E%7B2%7D%20%2B%202x%20-%203%20%3D%20%28x%20%2B%203%29%28x%20-%201%29%5C%5Cx%5E%7B2%7D%20%2B%205x%20%2B%206%20%3D%20%28x%20%2B%203%29%28x%20%2B%202%29)
We must find the least common multiple of the denominators. We take the maximum power of each separate factor.
Factors of first fraction = (x + 3) × (x - 1)
Factors of second fraction = (x + 3) × (x + 2)
LCM = (x + 3)(x - 1)(x + 2)
The lowest common denominator of the two fractions is (x + 3)(x - 1) (x + 2).
Answer:
-42.66666...
Step-by-step explanation:
-64 * 2/3 is -42.66666...
well, according to the calculator.
Answer:3+(-6)
Step-by-step explanation: